The effects of iron deficiency on neutrophil/monocyte apoptosis in children - (:unkn) unknown (WILEY, 2007)
Objectives: Iron is essential for DNA synthesis; its deficiency may lead to impaired DNA synthesis and subsequent alterations in levels of apoptosis. Here, we have aimed to investigate effects of iron deficiency anaemia (IDA) on apoptotic response of phagocytic cells and to understand whether the effect is reversible after iron supplementation. Materials and methods: Forty-nine IDA patients and 26 healthy controls, aged between 6 months and 12 years with similar demographic status, were considered. Neutrophil- and monocyte-apoptotic responses of IDA patients and the control group were compared by flow cytometry. Then, IDA patients were provided with oral iron supplementation. On day 15 of iron therapy, neutrophil- and monocyte-apoptotic responses of IDA patients were rechecked and were compared to those of control group. Results: Neutrophil- and monocyte-apoptotic responses in terms of early and late percentages of apoptosis, and percentages of necrotic cells, were significantly less in IDA patients compared to the control group. The significantly low apoptotic responses of IDA patients rose to levels of the control group by day 15 of iron therapy. Besides, the effect of IDA on apoptotic responses was found to be more enhanced in severe IDA patients that those of mild IDA patients. Conclusion: Correction of differences after iron supplementation therapy implies that IDA might be a cause for changes in neutophil- and monocyte-apoptotic responses. The impact of this diminution of apoptotic cellular function in IDA should be further investigated, with longitudinal studies, in order to document the impact of any severe and/or long-lasting IDA on autoimmunity and malignancy.
Keywords: RADIATION-INDUCED APOPTOSIS; P53-DEPENDENT APOPTOSIS; CELLS; ANEMIA; PREVALENCE; TURKEY; P53; DESFERRIOXAMINE; SCHOOLCHILDREN; THALASSEMIA